0281 Impact of chronic sleep disruption on glymphatic function, cognitive performance, and neuropathology in the 5xFAD mouse model. (25th May 2022) - Pedersen, Taylor; Keil, Samantha; Agarwal, Sanjana; Badran, Mohammad; Gozal, David; Iliff, Jeffrey
Abstract: Introduction: Recent studies suggest a bidirectional relationship between sleep disruption and Alzheimer's disease, with mid-life sleep disruption associated with the development of Alzheimer's-related amyloid and tau pathology. Yet, the mechanistic link between sleep disruption, particularly over chronic time scales, and the development of Alzheimer's pathology remains unclear. Methods: In this study, we evaluated the impact chronic sleep disruption has on the onset of cognitive impairment and neuropathologic disease progression using the 5xFAD amyloidosis mouse model. Chronic sleep disruption in male and female C57BL/6 and 5xFAD+ mice was performed in Lafayette sleep fragmentation cages from 10-18 weeks of age. Cognitive impairment was evaluated through behavioral tasks indicative of spatial memory, short-term memory, locomotion, anxiety, and activities of daily living. Upon completion of behavioral experiments, glymphatic function was assessed by measuring the influx of fluorescent cerebrospinal fluid tracers into brain tissue. Aquaporin-4 localization, amyloid plaque deposition, and markers of astroglial and microglial activation were assessed by immunofluorescence. Results: We observed that chronic sleep disruption impaired cognitive performance and increased neuropathological outcomes in 5xFAD+ and littermate controls. The impact on glymphatic function was assessed in parallel and correlated with neuropathological and behavioral outcomes. Conclusion: These findings highlight the critical association between dysfunctional sleep and the development of cognitive impairment and neuropathologic disease progression. They indicate that there is a potential interaction between inflammatory expression after chronic sleep disruption and neuropathologic disease progression. Support (If Any):